2023
DOI: 10.1038/s41598-023-29498-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thinning on soil nutrient availability and fungal community composition in a plantation medium-aged pure forest of Picea koraiensis

Abstract: Thinning is an important silvicultural practice for improving the productivity and wood production in plantation forest. Different intensities of thinning management can affect tree growth and alter soil nutrient effectiveness, thus affecting soil fungal community structure and diversity. Our objective is to determine the soil factors and their regulatory mechanisms that influence stand growth by thinning, and to provide data to support the establishment of large diameter timber cultivation technology for Pice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The functional and taxonomic diversity of fungi is important for ensuring the growth and resilience of plantations [44]. The thinning management of different intensities will affect tree growth, and change soil nutrient availability, and thus affect the composition and structure of soil fungal communities [45]. In our study, Basidiomycetes and Ascomycetes emerged as the dominant fungi across all plots, and our results are consistent with most studies [46,47].…”
Section: Responses Of Soil Fungal-community Structure To Crop-tree Th...supporting
confidence: 89%
“…The functional and taxonomic diversity of fungi is important for ensuring the growth and resilience of plantations [44]. The thinning management of different intensities will affect tree growth, and change soil nutrient availability, and thus affect the composition and structure of soil fungal communities [45]. In our study, Basidiomycetes and Ascomycetes emerged as the dominant fungi across all plots, and our results are consistent with most studies [46,47].…”
Section: Responses Of Soil Fungal-community Structure To Crop-tree Th...supporting
confidence: 89%
“…Results of Caihong, et al [38], in P. koraiensis plantation, evidenced as all medium (30%) and high (50%) intensity thinning treatments significantly increased soil nutrient content, including total carbon, total nitrogen, total phosphorus, total potassium, as well as available phosphorus and available potassium. Fungal diversity was higher in both thinned plots but lower in abundance than the control.…”
Section: Thinning Intensity Effects On Soil Chemical and Biochemical ...mentioning
confidence: 90%
“…Fungal diversity was higher in both thinned plots but lower in abundance than the control. The results of Caihong et al [38] evidenced that thinning intensity modulates biogeochemical cycles by affecting soil nutrients and fungal community structure. Wu et al [29] showed that thinning intensity, improved soil microbial abundance, because caused an in soil organic carbon.…”
Section: Thinning Intensity Effects On Soil Chemical and Biochemical ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pothier analyzed the growth of balsam fir forests and found that harvesting could significantly promote the growth of large-diameter trees [118]. Caihong reported that thinning can positively affect soil nutrients and fungal community structures and promote the growth of large-diameter trees [119]. Furthermore, the increase in large-diameter trees suggests the increase in the economic value of the forests under management guided by the equilibrium curves.…”
Section: Equilibrium Curvementioning
confidence: 99%